Brayton cycles as waste heat recovery systems on series hybrid electric vehicles. (15th July 2018) - Nader, Wissam Bou; Mansour, Charbel; Dumand, Clément; Nemer, Maroun
Highlights: Study assesses Brayton waste heat recovery systems on combustion engines for hybrid vehicles. An exergy analysis is conducted to identify the optimal system configuration. The intercooled Brayton cycle architecture is prioritized among investigated configurations. 5.5% and 7.0% fuel savings are observed on plug-in and self-sustaining series hybrid vehicles. Abstract: In the global attempt to increase the powertrain overall efficiency of hybrid vehicles while reducing the battery size, engine waste heat recovery (WHR) systems are nowadays promising technologies. This is in particular interesting for series hybrid electric vehicles (SHEV), as the engine operates at a relative high load and under steady conditions. Therefore, the resulting high exhaust gas temperature presents the advantage of increased WHR efficiency. The Brayton cycle offers a relatively reduced weight compared to other WHR systems and presents a low complexity for integration in vehicles since it relies on an open system architecture with air as the working fluid, which consequently avoids the need for a condenser compared to the Rankine cycle. This paper investigates the potential of fuel consumption savings of a SHEV using the Brayton cycle as a WHR system from the internal combustion engine (ICE) exhaust gases. An exergy analysis is conducted on the simple Brayton cycle and several Brayton waste heat recovery (BWHR) systems were identified. A SHEV with ICE-BWHR systems is modeled, where the recovered engine waste heat is converted into electricity using an electric generator and stored in the vehicle battery. The energy consumption simulations is performed on the worldwide-harmonized light-vehicles test cycle (WLTC) while considering the additional weight of the BWHR systems. The intercooled Brayton cycle (IBC) architecture is identified as the most promising for automotive applications as it offers the most convenient compromise between high efficiency and low integration complexity. Results show that 5.5% and 7.0% improved fuel economy on plug-in and self-sustaining SHEV configurations respectively when compared to similar vehicle configurations with ICE auxiliary power units. In addition to the fuel economy improvements, the IBC-WHR system offers other intrinsic advantages such as low noise, low vibration, high durability which makes it a potential heat recovery system for integration in SHEV.